ANALISIS JARINGAN KOMUNIKASI UNTUK MENUNJANG KEGIATAN PEMASARAN PADA INDUSTRI KECIL (COMMUNICATION NETWORK ANALYSIS TO SUPPORT SMALL INDUSTRY MARKETING) - Utami, Hamidah Nayati (Fakultas Ekonomi, UIN Maliki Malang, 2007)
Small industry marketing corelated with comunication process. There are communication process between consumer and producer. The situational factors are support the communication process in group. This situations are comnunication network, comnunication behavior, group cohessivity, size of group.Â This research aimed to describe communication process and marketing activity on small industry group of ceramics, and to examine the correlation of communication process and marketing activity on small industry group of ceramics. This study was conducted the craftsmen of ceramics at Dau district, Malang Regency. Sample taken with simple random sampling method. Survey and interview technique were implemented among 25 craftsmen. Data was analyzed by using communication network analysis and tau Kendall. The results indicated that the craftsmen had a high level of individual connectedness, a medium level of Individual Integration, but Individual Diversity was low. The level of intensity of craftsman marketing activity was low. The results indicated that of individual connectedness, a medium level of Individual Integration, but Individual Diversity were low were correlated with craftsmenâ€™s activity in promotion, product determining, placement, and pricing.